Genetics Divergence in Bhindi (Abelmoschus esculentus (L.) Moench) - Bindu K K (Department of Plant Breeding, College of Agriculture, 1993)
A study was conducted in the Department of Plant Breeding, College of Agriculture, Vellayani during the period 1991-93. The main aim was to estimate the magnitude of genetic divergence in a collection of bhindi varieties to select suitable ones for use as parents for developing commercial hybrid varieties. The estimation of genetic parameters of important economic characters, the association among these characters, direct and indirect effects and D2 values were undertaken. Seventy genotypes of bhindi were evaluated in a RBD with three replications. The genotypes showed significant differences in most of the characters studied except fruiting phase and leaf axil bearing the first flower. Genotypic coefficient of variation was maximum for weight of fruits per plant and minimum for days to first flowering. Heritability estimate was maximum for length of fruit while it was minimum for leaf axil bearing the first flower. Genetic advance as percentage of mean was maximum for weight of fruits per plant. High hertibility coupled with high genetic advance was recorded for length of fruit, leaf area, weight of single fruit, height of the plant and weight of the fruits per plant. At genotypic level yield per plant showed positive correlation with all the characters studied. Path coefficient analysis at genotypic level revealed that the number of fruits per plant, weight of single fruit and number of branches exhibited high direct influence on yield. The study indicated that the model for selection of high yielding varieties of bhindi should be based on the number of fruits per plant, weight of single fruit and number of branches. D2 analysis revealed that the 70 genotypes were grouped into six clusters. Cluster I, II, III, IV, V and VI contained fifty seven, four, three, two, three and one genotypes respectively. The maximum divergence was obtained between clusters II and VI and the minimum between clusters I and IV. The intra cluster distance was maximum in cluster III and minimum in cluster IV. In future breeding programme for the development of heterotic hybrids parent may be selected from cluster II and VI for hybridization.